3D structure-preserving galvanic replacement to create hollow Au microstructures. Issue 27 (29th June 2017) - Gatemala, Harnchana; Ekgasit, Sanong; Pienpinijtham, Prompong
Abstract : 3D hollow Au microstructures (HL-AuMSs) are fabricated via a galvanic replacement approach. 3D nanoporous Ag microstructures (np-AgMSs) are sacrificed as a template to control the structural complexity of HL-AuMSs. Abstract : For the first time, 3D complex hollow Au microstructures (HL-AuMSs) fabricated via a 3D structure-preserving galvanic replacement approach are presented. 3D nanoporous Ag microstructures (np-AgMSs) are employed as templates, which are galvanically replaced by Au 3+ under extremely high Cl − environments. During this galvanic replacement process, insoluble surface blocking AgCl species, is transformed under extremely high Cl − environments into a water soluble AgCl2 − complex, which is easily liberated from the Ag surface. Therefore, chloride ion is the key parameter in the 3D morphological preservation of these templates. The preferential galvanic replacement is observed at the tips of np-AgMSs templates due to high charge density. The wall thickness of HL-AuMSs can be easily controlled by varying the mole ratio of Au 3+  : Ag. This 3D structure-preserving galvanic replacement is not only applied for various morphologies of Ag templates, but also applied for other precious metals with excellent template morphology retention. Moreover, due to this stabilizer-free protocol, the fabricated HL-AuMSs show efficient catalytic activity for the reduction of p- nitrophenol by NaBH4 within 10 minutes for 6 cycles.